Legal Justice in Returning Losses to Victims of Illegal Investment Criminal Acts - Santoso, Bambang; Arifin, Muhammad; Ramlan, Ramlan (Faculty of Law, Universitas Pekalongan, 2024)
Regarding Legal Justice in Restitution of Victims of Criminal Acts, further provisions regarding the procedure for carrying out conditional sentences (voorwaardelijke veroordeling) are regulated in Article 276 of the Criminal Procedure Code which states: